Food Behaviour and Nutritional Status of Urban Primary School Children in Rajshahi Metropoliton City - Ali, Afsana; Haque, Md Jawadul; Amin, Md Nurul; Sharmin, Ashrafi; Kawsarunahar,; Ferdous, Jannatul (Ibrahim Cardiac Medical Journal, 2025)
Background & objective: Healthy dietary habits during childhood promote optimal physical, mental, emotional, and cognitive well-being of a child, and may contribute to the prevention of infectious and chronic diseases later in their life. Nevertheless, many factors prevent children from adopting healthy food behaviour and leading an active life. This study was undertaken to determine the nutritional status of the urban primary school children in Rajshahi Metropolitan City. Methods: The study was a descriptive cross-sectional study conducted in the Department of Community Medicine, Rajshahi Medical College, Rajshahi, over a period of one year between January to December 2019. The data collected from the PN Govt. Girls’ High School, and Rajshahi Collegiate School, Rajshahi, are both located in the Metropolitan area. A total of 270 primary school children of both sexes, aged 7-12 years who voluntarily consented through their school authority were included in the study. The nutritional status of the children was measured using BMI (calculated from their weight and height data). While the nutritional status of the children was the outcome variable, the age, sex, socioeconomic status, foods & dietary behaviour, exercise/activity, leisure-time activity and behaviours that adversely affect their health and nutritional status were the exposure variables. Result: The mean age of the children was 9.7 ± 1.2 years (range: 7-12 years). The boy-girl ratio was 6:4. The prevalence of overweight and obesity was 14.8 and 7.8% respectively. Approximately 58% of the students were maintaining a healthy weight for their age and sex. The prevalence of underweight and severely underweight were no less (14.1 and 5.6% respectively). While obesity among boys was somewhat higher (9.5%) than among girls (6.7%), severe underweight was more in girls (6.1%) than that in boys (4.8%). The majority (91.9%) of the students used to take three major meals a day. Most (83%) of the major meals contained rice, meat or fish, vegetables, and pulses. Over three-quarters (77.8%) reported taking vegetables and fruits every day with 77.4% having one serving of fruits daily. Over half (53.7%) of the students used to take soft drinks at least once a day and over 60% took fast-food 1-3 times a week. Students generally practiced some form of physical activity or sports with more than half (56.7%) taking exercise up to 30 minutes a day. Over three-quarters (75.2%) of students preferred outdoor games and the rest indoor games. Conclusion: Nearly two-fifths of the primary school children had healthy weights for their age and sex, one-fifth was underweight and another one-fifth were overweight or obese. Almost all the students practice some form of physical activity or sports. However, their food behavior is not as good as their exercise behaviour. Ibrahim Card Med J 2024; 14(1): 54-61